Strategi Pemasaran Bisnis Kuliner Menggunakan Influencer Melalui Media Sosial Instagram - Made Resta Handika; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACTCulinary Marketing Strategy Using Influencer Through Social Media Instagram (Case Study In Café Night Market & Co-Working Space). This type of research uses primary data and secondary data using Qualitative research design. The number of informants in this study is 9 people (3 Owners and 6 Visitors). The sample will be obtained by using purposive sampling technique. Data collection techniques can be done by interview (interview), questionnaire (questionnaire), observation (watch), and a combination of the three, in general from the respondents selected as a sample, which includes the identity data of respondents. Based on the results obtained by using qualitative analysis, it can be criticized in this research that the reason why the Night Market Café & Co-working Space Project is moving from conventional way to Instagram marketing that is, firstly because of technological progress, consumers are more inclined to use social media Instagram, second by using social media marketing especially Instagram can cost more in marketing financing, using more influence in Instagram, and give positive impact to progress of The Night Market Café & Co-working Space, last role variable of place / place in marketing mix can make visitors to come to Night Market Café & Co-working Space because Night Market Café & Co-working This space provides and presents the interior and atmosphere of the place that appeals to the consumer and also according to the bag of konaumen. Places that use less strategic researchers but with the advancement of technology and promotional strategies that Night Market Café & Co-working Space can be directly entrusted to the hearts of consumers